Glenn Gould's Goldberg Variations : A Transcription of the 1981 Recording of the Goldberg Variations by Johann Sebastian Bach - Bach, Johann Sebastian 1685-1750; Gould, Glenn 1932-1982; Hopkins, Nicholas (New York Carl Fischer, 2015)
This transcription of Glenn Gould's 1981 landmark recording of Johann Sebastian Bach's Goldberg Variations presents in notated form crucial aspects of Gould's performance practices with regard to this piece, in particular, tempos, ornamentation, dynamics and articulations. Also included are Gould's fingerings and pedalings. The edition features a newly edited and engraved "Urtext" version of the Goldberg variations on verso pages, accompanied by Gould's realization on recto pages. Pianists and harpsichordists will delight in the careful research behind the preparation of this critical edition.
"Urtext" version alternates with Gould's embellishments.
Introduction and critical notes in English.
Keywords: 18th Century (1701-1800); 20th Century (1901-2000); Theme and variations; Keyboard music; Performance; Germany